Aquatic and wetland monocotyledonous plants of Mexico - Lot, Antonio (Instituto de Ecología, A.C., 2012)
A review of the information on the richness and distribution of the Mexican aquatic and wetland (herbaceous) monocots, is presented, for the purpose of contributing to a better understanding of the flora distributed in the wetlands of the national territory. Three hundred eighty one species (392 taxa) belonging to 104 genera and 28 families, considered as strict aquatics or wetland plants, were registered; as well as 114 tolerant or facultative hydrophytes of lacustrine and pond habitats. Half of the 28 families correspond to taxa considered by most botanists as terrestrial, but they represent a large component of the Mexican aquatic flora (71% of the genera and 75% of the species). The endemics make up 14% of the monocots. Their presence throughout a great diversity of habitats and its representation in several vegetation types and communities, make them one on the most diverse ecological and geographical components in the American continent. About 46% of the species belong to meridional elements, while 25% correspond to boreal one; while the Mexican element (13.9%) is equivalent to the sum of the cosmopolitan and introduced species.